2013
DOI: 10.1246/bcsj.20130067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopants Pr and La on the Catalytic Activity of Cerium Oxide for Soot Oxidation

Abstract: Effects of rare earth or transition metal doping on the activity of CeO2 to particulate matter oxidation were investigated, and it was found that a Ce–Pr–La–O mixed oxide demonstrates the lowest ignition temperature of carbon, as low as 550 K. Oxygen-temperature-programmed desorption measurements suggested that the amount of O2 desorbed from CeO2 increases with the substitution of Pr, and furthermore, La doping reduces the desorption temperature of the lattice oxygen. Even in the absence of oxygen, carbon oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The increase in nonstoichiometry in N 2 atmosphere may depend on the mobility of oxide ions enhanced by the excessive oxygen vacancies formed by Pr 3+ and La 3+ rather than the number of redox centers. In our previous study, La doping induced a decrease in the onset temperature of carbon oxidation, and the lowest temperature was observed at 15 mol % La. This trend agrees well with the observation of nonstoichiometry in N 2 atmosphere in this study (Figure ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in nonstoichiometry in N 2 atmosphere may depend on the mobility of oxide ions enhanced by the excessive oxygen vacancies formed by Pr 3+ and La 3+ rather than the number of redox centers. In our previous study, La doping induced a decrease in the onset temperature of carbon oxidation, and the lowest temperature was observed at 15 mol % La. This trend agrees well with the observation of nonstoichiometry in N 2 atmosphere in this study (Figure ).…”
Section: Resultssupporting
confidence: 93%
“…The differences in the dopant ionic size and valence affect various factors such as particle size, phase modification, structural defects/distortion in the lattice, and chemical nonstoichiometry. 21 In our previous study, 22 we found that a ternary oxide (Ce− Pr−La−O) demonstrates a low ignition temperature for carbon (as low as 550 K). The oxygen temperature-programmed desorption (TPD) measurements showed that lattice oxygen desorption from CeO 2 increases with Pr substitution and the desorption temperature of lattice oxygen decreases with La doping.…”
Section: ■ Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The O2 evolved amounts further increased by substituting Pr in the ceria lattice, consistent with data reported by other authors [26,55], whatever the preparation method considered. This can be attributed to a mixed valence state of Pr, that is, +3 and +4 [54,56]. Therefore, total O2 amounts evolved from the catalysts increase with the praseodymium content, but not in a gradual way, as will be commented below.…”
Section: O2-tpd Analysismentioning
confidence: 87%
“…[52] Thus, the ignition temperature is generally recognized as an important indicator of soot combustion reactivity.I nt his study,C uMnO(K) shows al ower ignition temperature for soot combustion than CuMnO, maybeb ecause the amount of low-temperature-desorbed oxygen species (130-340 8C) from CuMnO(K) is higher than that from CuMnO (see O 2 -TPD curvesi nF igure 9a), as such low-temperature-desorbed oxygen, which acts as the reactive species, will contributetothe ignition of sootcombustion. [53] The resultso ft he soot temperature-programmed reduction (TPR) measurement are shown in Figure 9b.T he reduction peak temperature of CuMnO(K) is slightly lower than that of CuMnO,w hich demonstrates the improved reducibility by soot of the reactive oxygen species,w hichi sf avorable for the enhancemento ft he catalytic activity. [54] The CO 2 -TPD curves ( Figure 9c)f or CuMnO and CuMnO(K) both show al ow-temperature peak ( % 72 8C) relatedt op hysically adsorbed CO 2 and several high-temperature peaks (300-600 8C), whichc an be assigned to chemically adsorbed CO 2 .N otably,t he low-tempera- www.chemcatchem.org ture desorption peak for CuMnO(K) is more intense than that of CuMnO, maybe because of the higher specific surfacea rea of CuMnO(K) in comparison to CuMnO( 18 vs. 8m 2 g À1 ).…”
Section: Surfacec Hemicalp Ropertiesmentioning
confidence: 99%